Ancient Divination and Experience - Driediger-Murphy, Lindsay; Eidinow, Esther (Oxford University Press, 2019)
The introduction to this volume describes the contribution that it makes to scholarship on ancient divinatory practices. It analyses previous and current research, arguing that while this predominantly functionalist work reveals important socio-political dimensions of divination, it also runs the risk of obscuring from view the very people, ideologies, and experiences that scholars seek to understand. It explains that the essays in this volume focus on re-examining what ancient people-primarily those in ancient Greek and Roman communities, but also Mesopotamian and Chinese cultures-thought they were doing through divination. The Introduction provides an overview of the content of each chapter and identifies key themes and questions shared across chapters. The volume explores the types of relationships that divination created between mortals and gods, and what this can tell us about the religions and cultures in which divination was practised.